(untitled) (International Journal of Engineering and Computer Science, 2017)
This paper cover what is Spoofing, MAC spoofing; why people use it. This paper is a survey on MAC Spoofing. This paper have an overview of spoofing characterized , Vulnerabilities, working and operation , Detection of MAC Spoofing, Address Resolution Protocol. MAC spoofing. Mac spoofing is computer identity theft, for good or for bad reasons, and it is relatively easy. MAC spoofing has an address on a NIC (network interface card) ; it is inbuilt on NIC. A MAC Spoofing is to view the nextgeneration technology of IT industry. MAC Spoofing is applying to future spoofing servic